The combination of mare's milk and grape polyphenol extract for treatment of dysbiosis induced by dextran sulfate sodium - Samat Kozhakhmetov; DMITRIY BABENKO; MADIYAR NURGAZIYEV; ALTYNAY TUYAKOVA; AYAULYM NURGOZHINA; NURISLAM MUHANBETGANOV; LAURA CHULENBAYEVA; SHYNGGYS SERGAZY; ALEXANDR GULYAYEV; TIMUR SALIEV; ALMAGUL KUSHUGULOVA (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Kozhakhmetov S, Babenko D, Nurgaziyev M, Tuyakova A, Nurgozhina A, Muhanbetganov N, Chulenbayeva L, Sergazy S, Gulyayev A, Saliev T, Kushugulova A. 2020. The combination of mare's milk and grape polyphenol extract for treatment of dysbiosis induced by dextran sulfate sodium. Biodiversitas 21: 2275-2280. This study showed the potential of a biological product based on mare's milk and a complex of grape polyphenols to modulate intestinal microflora after dextran sulfate sodium  (DSS)-induced dysbiosis. Rat ulcerative colitis has been developed using intra-gastric administration of 10% DSS solution. To track changes in the structure of the microbiome at all stages of the study, the next-generation sequencing of the 16S rRNA gene section and LotuS conveyor were used. The results of sequencing demonstrated a decrease in biological diversity of microbiota after the induction of colitis, and recovery after 7 days of use of the  (MMGPE). The product induced the structural changes of the microbiome damaged by DSS. Representatives of SCFA producing bacteria increased concentrations of  Prevotella, Alloprevotella, Lactobacillus, Ruminococcaceae, and Blautia.